Evaluation of The Implementation of The Smart School Transportation Program (ACS) in Ponorogo Regency - Pangestu, Rizky Purna Aji Galih; Sudibyo, Desiderius Priyo; Nugroho, Rino Ardhian (Future Science / FSH-PH Publications, 2023)
Smart School Transportation (ACS) is a program from the Ponorogo Regency Government as an effort to make it easier for students to get free school transportation. The purpose of this research is to describe the evaluation of the implementation of the ACS Program and to describe the inhibiting and supporting factors for the implementation of the ACS program in Ponorogo Regency. This type of research is descriptive qualitative. Data analysis techniques Qualitative analysis is carried out through data collection, data reduction, data presentation, and withdrawal conclusion. The results of the study show that the ACS program in the District Ponorogo is still not running effectively. In terms of effectiveness, it has not been effective because there are still many underage children who use motorbikes. The efficiency aspect has been fulfilled because it has implemented cost and time efficiency in program operations. In the aspect of adequacy still not fulfilled because of the limited number and capacity of the fleet in transporting students. In the aspect of alignment it is still not evenly distributed because there are still many schools that have not received program services. The responsiveness aspect has received response and support from ACS users and parents. Aspects of provisions, programs This ACS is right on target, namely to transport students. In the implementation of the ACS program, of course, there are inhibiting and supporting factors. The inhibiting factor for the first ACS program was resources, because human resources in the form of Department of Transportation staff were inadequate to carry out socialization and financial resources were also inadequate, which affected the provision of fleets and the provision of program support facilities. The second inhibiting factor is the bureaucratic structure due to the absence of Standard Operating Procedures (SOP) that are clear and regional regulations that cover program implementation. While the supporting factors for the implementation of the first ACS program, namely, communication through transmission and clarity of information have been running optimally. The second supporting factor is the attitude of the implementer that liveliness officer executor socialization from Service Communications Ponorogo Regency for schools and students is carried out continuously every new school year.